1985
DOI: 10.1159/000242091
|View full text |Cite
|
Sign up to set email alerts
|

Lipolytic Activity of Renal Cortex during Ontogenetic Development in Rats

Abstract: The lipolytic activity of rat kidney cortex was investigated in newborn and adult rats. Two peaks of lipolytic activity could be detected at pH 5.0 and 8.4, respectively. Lipase activity at pH 5.0 is completely inhibited by 0.2 M sodium fluoride and can be stimulated by norepinephrine (10 μg/ml). Full activity is already present in 5-day-old rats. The response to sodium fluoride and norepinephrine is identical in newborn and adult animals. Lipase activity at pH 8.4 is inhibited up to 85% by 0.6 M sodium chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
1
1
Order By: Relevance
“…This particular problem has previously been observed by others. When performing microdialysis of lipophilic substances Groth and co-workers observed that the recovery of sodium fusidate increased with increasing concentrations, probably due to interaction between the membrane and sodium fusidate [13]. However, in our hands the addition of 0.25% BSA to the perfusion fluid resulted in a concentration independent recovery, indicating that some sort of binding took place without added BSA.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…This particular problem has previously been observed by others. When performing microdialysis of lipophilic substances Groth and co-workers observed that the recovery of sodium fusidate increased with increasing concentrations, probably due to interaction between the membrane and sodium fusidate [13]. However, in our hands the addition of 0.25% BSA to the perfusion fluid resulted in a concentration independent recovery, indicating that some sort of binding took place without added BSA.…”
Section: Discussioncontrasting
confidence: 46%
“…Following 70 min of baseline sampling, an intraperitoneal injection (1 mg/kg) of the specific ␤ 3 -adrenerg agonist, BRL37344, was given at time 0 min, in order to stimulate lipolysis. Plasma samples were taken at time: −70, −10, 10, 70, 110 and 150 min in EDTA-coated tubes containing NaF to prevent lipolysis during storage [13]. After termination of the experiment the probe was carefully removed and the rat was decapitated.…”
Section: In Vivo Microdialysis Experimentsmentioning
confidence: 99%